FACTORS INFLUENCING ON CONSUMERS’ ATTITUDE TOWARDS THE DAIRY PRODUCTS: A CASE STUDY OF HIGHLAND BRAND PRODUCTS IN VAVUNIYA DISTRICT - Pushpanathan, A.; Priyanthy, M. (IFRSA, 2012)
As a consumer, they have to be more vigilant about prevailing market situations, availability of goods and quality and standards of goods. Consumers have the ultimate power to choose the right products which are fulfill their needs. Further there are internal factors such as personality, attitude, perception, learning and memory influencing on their purchase decision. Likewise cultural, social and situational factors also the determinant factors on their purchase behavior. An attitude describes a person’s relatively consistent evaluations, feelings, and tendencies towards an object or an idea. Attitudes put people into a frame of mind for liking or disliking things and moving towards or away from them. Marketers need to know what attitudinal barriers exist in purchasing so they can strategize how to counter those obstacles through marketing activities. The main objective of this study is to analysis the factors influencing on consumers’ attitude towards the Highland brand in products post war era. The quality, price, nutritional value, availability, packaging are considered independent variables, and consumers’ attitude considered as a dependent variable of this study. 60 customers were randomly selected in the Vavuniya Town area and the questionnaire was issued among them. Data were entered in to the SPSS package. For measuring the reliability of data the Cronbach Alba was calculated. The Cronbach Alpha of this study is 0.88. It is greater than the cut off rate. Linear Regression Analysis was used to measure the relationship between independent variables and dependent variable (R2 = 0.600). The finding was indicated that the quality of the highland product have more impact than the other factors such as price, nutritional value, availability and packaging on purchasing the Highland branded products post war era in Vavuniya Town Area.
Keywords: Quality; Price; Nutritional Value; Availability; Packaging; consumers’ attitude